An integrated modeling approach for atmospheric corrosion in presence of a varying electrolyte film. (1st January 2016) - Van den Steen, N.; Simillion, H.; Dolgikh, O.; Terryn, H.; Deconinck, J.
Abstract: A Dynamic Electrolyte Film Corrosion (DEFC) model is presented that integrates a model for uniform film condensation/evaporation in presence of salts with a simple model of iron corrosion. The focus is on the role of the film thickness. A limited number of measurements confirms that it is unavoidable to consider the hygroscopic effects. The model is used to simulate the role of sample thickness, heat transfer and changing rates of temperature and relative humidity in well defined climate chamber conditions. Obtained film thicknesses and corrosion rates are simulated using identical input data in absence of salt and for two salts (NaCl and a seawater-like mixture of 90 %NaCl-10 %MgCl2 ). The large indirect influence of salts on the corrosion is discussed. Also one-week simulations are performed based on recorded and averaged meteorological data. They show that averaged meteorologic data will lead to incorrect results.